Selected statistics on African countries. - African Development Bank. Statistics Department (Tunis, Tunisia : African Development Bank, Statistics Dept., 2007)
An annual publication of the African Development Bank Group, presenting data on major development indicators of African economies. Part one gives cross country statistics on selected indicators and part two provides country-specific time series data all the countries in the continent.
Text in English and French.
Description based on first issue; title from disc label.
oif 24/02/15
Ref.
Keywords: Africa -- Economic conditions -- Statistics -- Periodicals; Economic indicators -- Africa -- Periodicals